(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Early detection of tumors at preclinical stages is a key factor in reducing cancer-related morbidity and mortality. Among modern diagnostic methods, ultrasound imaging plays a crucial role due to its non-invasive nature, accessibility, safety, and cost-effectiveness. Ultrasound allows the visualization of structural changes in tissues before the appearance of clinical symptoms, enabling timely diagnosis and early therapeutic intervention. Advances in ultrasound technologies, including Doppler imaging, elastography, and contrast-enhanced ultrasound, have significantly improved diagnostic accuracy and sensitivity. This article analyzes the role of ultrasound in the early detection of tumors, highlights its advantages and limitations, and discusses its significance in preventive oncology and screening programs.